Pregabalin Add-On vs. Dose Increase in Levetiracetam Add-On Treatment: A Real-Life Trial in Dogs With Drug-Resistant Epilepsy - Kriechbaumer, Sandra R. P.; Jurina, Konrad; Wielaender, Franziska; Schenk, Henning C.; Steinberg, Tanja A.; Reese, Sven; Buhmann, Gesine; Doerfelt, Stefanie; Potschka, Heidrun; Fischer, Andrea (Frontiers in Veterinary Science, 2022)
Epilepsy is a common neurological disorder affecting 0.6–0.75% of dogs in veterinary practice. Treatment is frequently complicated by the occurrence of drug-resistant epilepsy and cluster seizures in dogs with idiopathic epilepsy. Only few studies are available to guide treatment choices beyond licensed veterinary drugs. The aim of the study was to compare antiseizure efficacy and tolerability of two add-on treatment strategies in dogs with drug-resistant idiopathic epilepsy. The study design was a prospective, open-label, non-blinded, comparative treatment trial. Treatment success was defined as a 3-fold extension of the longest baseline interseizure interval and to a minimum of 3 months. To avoid prolonged adherence to a presumably ineffective treatment strategy, dog owners could leave the study after the third day with generalized seizures if the interseizure interval failed to show a relevant increase. Twenty-six dogs (mean age 5.5 years, mean seizure frequency 4/month) with drug-resistant idiopathic epilepsy and a history of cluster seizures were included. Dogs received either add-on treatment with pregabalin (PGB) 4 mg/kg twice daily (14 dogs) or a dose increase in levetiracetam (LEV) add-on treatment (12 dogs). Thirteen dogs in the PGB group had drug levels within the therapeutic range for humans. Two dogs in the PGB group (14.3%; 2/14) and one dog in the LEV group (8.3%; 1/12) achieved treatment success with long seizure-free intervals from 122 to 219 days but then relapsed to their early seizure frequency 10 months after the study inclusion. The overall low success rates with both treatment strategies likely reflect a real-life situation in canine drug-resistant idiopathic epilepsy in everyday veterinary practice. These results delineate the need for research on better pharmacologic and non-pharmacologic treatment strategies in dogs with drug-resistant epilepsy.